Synthesis and studies of complex compounds of carboxyl-derivatives of methylphloroglucinol with metals - Kovalchukova, Olga; Absalan, Yahya; Bobylev, Sergey; Kuznetsov, Dmitry; Kobrakov, Konstantin (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Ten new complexes of 2,4,6â€“trihydroxy-3-methyl benzoic acid (methylphloroglucinol, L1) and 2,4,6â€“trihydroxy benzoic acid (phloroglucinol, L2) are isolated in the solid state, and their formulae were detected. The spectroscopic methods indicate that the coordination ofÂ L1 and L2 to the metallic ions occurs through one of the O-atom of the deprotonated carboxylic group and an O atom of the non-deprotonated neighboring hydroxy-group (bidentate chelating coordination). The schemes of the structure of complexes are proposed. The complex formation in solution is studied, and formation constants are calculated. It is shown that for the metal complexes of the 1st transitional series, the formation constants for the complexes are arranged as Mn(II) < Co(II) < Ni(II) < Cu(II) > Zn(II). The obtained results correlate with the Irving-Williams Series.